SCIENTIFIC-THEORETICAL INTERPRETATIONS OF THE SHORT GENRE (World Bulletin of Social Sciences, 2025)
The article examines in detail the scientific and theoretical interpretations of the short story genre. In particular, the history of short stories, the lexical meanings of the terms short story and narrative, the place of the short story genre on the border between the story and the novel, and the characteristics of the genre are studied. The influence of religious stories, folk tales, and written classical short stories on the formation of Uzbek short stories is also studied.